2016
DOI: 10.1002/pssb.201600442
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of zinc anode corrosion for printed flexible zinc‐air battery

Abstract: Self‐discharge caused by hydrogen evolution reaction (HER) coinciding with corrosion of the zinc anode is a major drawback of printed zinc‐air batteries. Thus, this work aims at suppressing self‐discharge of flexible printed zinc‐air batteries by coating thin layer of aluminum oxide (Al2O3) onto the surface of zinc particles. The Al2O3 coating layer was directly synthesized onto the zinc particles by a low‐cost and facile sol–gel method. The Al2O3 coating effectively mitigated HER of the zinc particles, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…Then, this particle sample was dried in oven at 100 °C for 10 h to remove excess water. Finally, the obtained nanoparticles were calcined in muffle furnace with a heating rate of 2 °C min −1 to 900 °C and kept for 5 h, after which the sample was naturally cooled down to room temperature to obtain the product sample (ZrO 2 nanoparticles) 65…”
Section: Methodsmentioning
confidence: 99%
“…Then, this particle sample was dried in oven at 100 °C for 10 h to remove excess water. Finally, the obtained nanoparticles were calcined in muffle furnace with a heating rate of 2 °C min −1 to 900 °C and kept for 5 h, after which the sample was naturally cooled down to room temperature to obtain the product sample (ZrO 2 nanoparticles) 65…”
Section: Methodsmentioning
confidence: 99%
“…Aluminate can be conveniently coated on Zn particles by sol-gel method using Al-isopropoxide as Al precursor, which effectively reduces the corrosion current of Zn by nearly five folds (112.1 vs 525.4 µA cm −2 ). [105,106] Other metal oxide coatings were also evaluated. A Bi 2 O 3 coating can greatly improve the cumulative Zn utilization rate from 85% of uncoated Zn particles to 465%.…”
Section: Compositional Optimization Of Zn Electrodesmentioning
confidence: 99%
“…During discharge, the zinc granules is oxidized to form zincate ion 20 . Consequently, saturated zincate ion can precipitate as solid zinc oxide on the active zinc surface.…”
Section: Resultsmentioning
confidence: 99%
“…Several research works revealed that coating zinc particles with various additives could overcome these issues 1719 . Aluminum oxide (Al 2 O 3 ) as a surface modification exhibited the positive effect on controlling the hydrogen evolution reaction (HER) for zinc-air batteries 20 . Besides, Al 2 O 3 coating layer prevents direct exposition of zinc to the KOH electrolyte leading to a significant decrease of self-discharge and hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%